The Effect of Fluoride and Iron Content on the Clinkering of Alite-Ye’elimite-Ferrite (AYF) Cement Systems - Isteri, Visa; Ohenoja, Katja; Hanein, Theodore; Kinoshita, Hajime; Illikainen, Mirja; Tanskanen, Pekka; Fabritius, Timo (Frontiers in Built Environment, 2021)
Alite–ye’elimite–ferrite (AYF) cement is a more sustainable alternative to Portland cement (PC) that may offer improved mechanical, rheological, and chemical performance. Using traditional raw materials and conventional clinker processing conditions, alite (C3S) and ye’elimite (C4A3$), the major phases in PC and calcium sulfoaluminate (CSA) cements, respectively, cannot be coproduced. The typical formation temperature in the kiln for alite is >1350°C, but ye’elimite normally breaks down above 1300°C. However, with careful composition control and in the presence of fluoride, alite can be mineralized and formed at lower temperatures, thus enabling the production of AYF clinkers in a single stage. In this study, the production of AYF cement clinkers with different chemical compositions is attempted at 1250°C. The sensitivity of the fluoride content is initially assessed with a fixed target clinker composition to determine the optimal requirements. The effect of altering the target ferrite (C4AF) and alite (C3S) contents is also assessed followed by the effect of altering the target C4AF and C4A3$ contents. It is shown that AYF clinkers can be produced in a single stage through the careful control of the fluoride content in the mix; however, the formation/persistence of belite and mayenite could not be avoided under the conditions tested. It is also shown that ∼10 wt% ferrite in the target composition provides sufficient AYF clinker burnability and the amount of fluoride needs to be controlled to avoid stabilization of mayenite.